External Debt and Pro-Poor Growth - Rolf Maier (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
To reveal effects and consequences of high indebtedness on income poverty, this paper explores empirically a linear and non-linear impact of external debt on pro-poor growth in developing and transitional countries. To examine this hypothesis, we test the distribution effect of external debt to GDP, external debt to exports, and debt services to exports on the poorest 20 and 20 to 40 percent in a crosscountry approach. In addition, we estimate the total effect, i.e. the distribution and growth effect, to analyse potential trade-offs between the impact of unsustainable external debt levels on poverty through overall economic growth and via distribution. To test the poverty effects, we collect an irregular and unbalanced panel of time-series cross-country data on the first and second quintile of 58 developing and transitional countries for the period 1970 - 1999. We apply two econometric specifications, a growth equation and a system GMM estimation, to cover econometric issues, cross-country variation and dynamic aspects of within-country changes of the income of the poor. Empirical findings of the impact of the debt indicators on pro-poor growth have to be interpreted carefully due to inconsistent results of the sensitivity analyses. Thus results do not indicate an optimal external debt level with respect to pro?poor growth. On the contrary, higher external debt levels are associated with negative effects on the level of the income of the poorest 40 percent without exhibiting any significant effects on the growth rates. Thus concise policy recommendations with respect to debt sustainability levels and debt relief are difficult. A cautious conclusion would be that debt relief may affect the poor positively, but seems not to be a sufficient policy instrument for improved growth rates of the income of the poorest 40 percent. This policy proposal would be in line with calls for more poverty-targeted capital inflows, as even total debt relief would release only insufficient resources for poverty reducing activities. With this interpretation, however, we abstract from political economy and bad governance issues which may prevent poverty reducing debt relief initiatives.
Keywords: 330